Trophic interactions of the Guttural Toad (Sclerophrys gutturalis, Power 1927) along an invasion gradient - Peta, Samuel Tebogo Posie (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.